Pain and the brain: Specificity and plasticity of the brain in clinical chronic pain - Apkarian, A.V. (2010)
We review recent advances in brain imaging in humans, concentrating on advances in our understanding of the human brain in clinical chronic pain. Understanding regarding anatomical and functional reorganization of the brain in chronic pain is emphasized. We conclude by proposing a brain model for the transition of the human from acute to chronic pain.